Hemodynamic and Hematologic Effects of Histotripsy of Free-Flowing Blood: Implications for US-mediated Thrombolysis - Devanagondi, Rajiv (J Vasc Interv Radiol, 2015)
PURPOSE: Histotripsy employs pulsed cavitational ultrasound for non-invasive tissue ablation. Some forms of therapeutic ultrasound cause intravascular hemolysis. We investigated the extent and consequences of histotripsy induced hemolysis in vivo. MATERIALS AND METHODS: Porcine femoral venous blood was treated with histotripsy in 11 animals with systemic heparinization and 11 without heparin. Serum and hemodynamic measurements were obtained at 0, 2, 5, 10, 15, 30 minutes, and 48–72 hours post-procedure. Fischer’s exact test was used to determine differences in mortality between heparinized and non-heparinized groups. A linear mixed effects model was used to test for differences in blood-analytes and hemodynamic variables over time. RESULTS: Of 11 non-heparin treated animals, 5 died during or immediately following histotripsy (non-heparin mortality 45% vs. heparin mortality 0%, p=0.035). Serum hematocrit, free hemoglobin, LDH, and right ventricular systolic pressure (RVSP) changed significantly (p<0.001) over the treatment time. Serum hematocrit decreased slightly (32.5 ± 3.6 to 29.4 ± 4.2%), while free hemoglobin (6.2 ± 4.6 to 348 ± 100 mg/dL), LDH (365 ± 67.8 ± to 722 ± 84.7 U/L), and RVSP (23.2 ± 7.2 to 39.7 ± 12.3 mmHg) increased. After 48 to 72 hours, hematocrit remained slightly decreased (p=0.005), while LDH and free hemoglobin remained slightly increased compared to baseline (both p<0.001). CONCLUSION: Intravascular histotripsy applied to free flowing venous blood is safe with systemic heparinization, causing only transient hemodynamic and metabolic disturbances, thereby supporting its use as a future non-invasive thrombolytic therapy modality.